IMPLEMENTASI BAURAN PEMASARAN TERHADAP UMKM KULINER DI WILAYAH KELURAHAN MERUYA SELATAN - Alvita Sari (Universitas Mercu Buana, 2022)
ABSTRACTThis community service program is motivated by the many Culinary MSMEs in the South Meruya sub-district area which have difficulties in the marketing aspect. Based on the conditions above, efforts need to be made to help culinary MSMEs get up and improve their business activities so that their productivity and turnover will gradually increase again. For this reason, the Community Service Team from the Faculty of Economics and Business, Mercubuana University, Jakarta, consisting of lecturers and students, helps culinary MSMEs, especially in the South Meruya Village, Kembangan District, West Jakarta with the